Slow work: The mainstream concept - Silvestre, M. J.; Gonçalves, S. P.; Velez, M. J. (Social Sciences, 2024)
The global acceleration of the pace of life has led to an increase in working hours, time pressure, and intensification of work tasks in organisations, with consequences for the physical and psychological health of workers. This acceleration and its consequences make it especially relevant to consider the principles of the slow movement and how they can be applied to the work context, focusing on the importance of slowing down the current pace of work and its implications for the sustainability of people and organisations. The key purpose of this study is to define the concept of slow work and understand its relationship with individual and organisational factors in order to extract the structuring dimensions, enabling its empirical study and practical application. Using grounded theory methodology, we conducted 12 semi-structured interviews with leaders of organisations from different sectors. Data analysis was performed using the MAXQDA programme. It was concluded that slow work is a way of working that respects the balance between individual rhythms and the objectives of the organisation, in favour of the sustainability of both parties, and that advocates qualitative goals, thinking time, individual recovery, purpose, and the humanisation of work. The main contribution is the conceptualisation of a construct that may be used in future studies, as well as in the development of organisational policies promoting the slow work culture.